The research landscape of the quality of life or psychological impact on gynecological cancer patients: A bibliometric analysis - Zhao, Jiayuan; Kong, Yujia; Xiang, Yang; Yang, Junjun (Frontiers in Oncology, 2023)
Background Gynecological cancer is one of the most common cancers in women. The quality of life (QoL) or psychological impact has emerged as an outcome indicator in many clinical trials of gynecological cancer and gained much concern in the clinical setting at the start of the 21st century. Our paper conducted a bibliometric analysis of QoL or psychological impact on gynecological cancer patients to show the status and hotspots. Methods Related publications from 2000 to 2022 were included by screening from the Web of Science Core Collection (WOSCC) on 26 June 2022. The bibliometrics was analyzed and visualized by bibliometrix R-package, VOSviewer, and CiteSpace V. Results A total of 6,479 publications were included in our study. The publications in this field were increased annually. The United States (n = 2,075) was the country with the most published papers. Sydney University (n = 167) was the most productive affiliation. Gynecologic Oncology and Journal of Clinical Oncology were the most relevant and most cited sources, respectively. The article written by Bray F et al. has the highest citation. Kim J and Aaronson NK ranked first in most productive author and most co-cited author, respectively. The keywords “mortality”, “fertility preservation”, and “palliative care” have bursts till 2022, which represented the frontiers of this field. Conclusion Our study provides an overall analysis of QoL or psychological impact on gynecological cancer patients, which can serve as a reference in future research.